My sister is 14 years old. my brother says that his age minus 12 equal to my sister's age.

Answers

Answer 1
Answer:

Answer:

26 years old.

Step-by-step explanation:

First lets write an expression for this problem.

That will be 14 + 12 = x

You will do this because it says how the persons sister's age is 14. And the brother says that his age is 12 minus equal to his sister's age. So that's why you use that expression.

So 14 + 12 will give yo 26.

So that means the brother is 26 years old.


Related Questions

What is the answer for this
Please Answer Now Identify the function’s vertical asymptotes. h(x)=x-4/x^2-4 x = 2 x = 4 x = -2, x = 2 x = -4, x = 4
Write 5,806 in scientific notation.
Add. Write your answer in simplest form. 4 6/7 + 3 5/7=____
Cheyanne plans to put $150 into a savings account. she can place her money into an account represented by f(x)=5x+150, or into another account represented by g(x)=150(1.03)^x. which account has the highest value in 3 years? which account has the highest value in 10 years?1. f(x) has the highest value in 3 years; g(x) has the highest value in 10 years 2. g(x) has the highest value in 3 years; f(x) has the highest value in 10 years 3. f(x) has the highest value in 3 years; f(x) has the highest value in 10 years 4.g(x) has the highest value in 3 years; g(x) has the highest value in 10 years

Simplify the following radical expression:
√20

Answers

Answer:

the answer is 2√  5

Answer:

4.472135955

Step-by-step explanation:

Factor completely 5x(x + 3) + 6(x + 3).(x + 3)(30x)

(x + 3)(5x + 6)

(x + 3)(11x)

Prime

Answers

Answer:

Option 2 is correct.    

Step-by-step explanation:

Given the expression 5x(x + 3) + 6(x + 3).

We have to factorize the expression completely.

Expression is

5x(x + 3) + 6(x + 3)

Take the factor (x+3) common from both the terms, we get

(x+3)(5x+6)

Hence, option 2 is correct.       

5x(x+3)+6(x+3) = (5x+6) (x+3) = (x+3)(5x+6)

Find y on the triangle that has sides length of 7 and x

Answers

The lengths of two sides is not enough information to determine a unique triangle. There are an infinite number of possible correct answers.

If the function G(x) = (x - 8)2 + 6 has the same shape as F(x) = x2 + 6, how far to the right of F(x) is G(x) shifted?

Answers

G(x) = (x - 8)^2 + 6\ \ \ and\ \ \ F(x) = x^2 + 6\n\nAns.\ G(x)\ is\ shifted\ 8\ units\ right\ to\ the\ F(x)

The triangles shown are similar.What is the value of x?



A.
12

B.
15

C.
20

D.
13

Answers

15, because 3 goes into 9, 3 times and, 4 goes into 12, 3 times therefore x has to follow this rule because these 2 triangles are similar and because it already gives you 5 just take 5*3=15 there is your answer enjoy!=)
(x)/(9)=(5)/(3)\n(x)/(9)=(15)/(9)\nx=15

Which measurement is most accurate to describe the length of a ladybug?9 mm
15 cm
0.5 m
3 km

Answers

9 mm it's the smallest measurement listed.